Increased risk of benign paroxysmal positional vertigo in patients with anxiety disorders: a nationwide population-based retrospective cohort study. Issue 1 (December 2016) - Chen, Zi-Jun; Chang, Cheng-Ho; Hu, Li-Yu; Tu, Ming-Shium; Lu, Ti; Chen, Pan-Ming; Shen, Cheng-Che
Abstract Background The objective of this study was to evaluate the risk of benign peripheral persistent vertigo (BPPV) among patients with anxiety disorders by using the Taiwan National Health Insurance Research Database (NHIRD). Methods We conducted a retrospective study of 15, 470 participants (7735 anxiety disorder patients and 7735 control patients) selected from the NHIRD. Patients were observed for a maximum of 9 years to determine the rates of newly diagnosed BPPV. A Cox regression model was used to evaluate the risk of BPPV among the patients with anxiety disorders. Results During the 9-year follow-up period, 178 (2.05 per 1000 person-years) anxiety disorder patients and 71 (0.81 per 1000 person-years) control patients were diagnosed with BPPV. The incidence risk ratio of BPPV between anxiety disorder patients and control patients was 2.52 (95 % confidence interval [CI], 1.90–3.37, P  < .001). After adjustment for age, sex, and comorbidities, patients with anxiety disorders were found to be 2.17 times more likely to develop BPPV (95 % CI, 1.63–2.90, P  < .001) than the control patients. Furthermore, female sex (HR = 1.81, 95 % CI, 1.31–2.50, P  < .001) and cerebrovascular disease (HR = 1.53, 95 % CI, 1.00–2.34, P  = .050) were independent risk factors for developing new-onset BPPV in patients with anxiety disorders. Conclusions Anxiety disorder patients may have an increased risk of developing BPPV, especially those who are female or have cerebrovascular disease.